2010
DOI: 10.1073/pnas.1004809107
|View full text |Cite
|
Sign up to set email alerts
|

Sequence dependence of DNA bending rigidity

Abstract: For many aspects of DNA-protein interaction, it is vital to know how DNA bending rigidity (or persistence length, a) depends on its sequence. We addressed this problem using the method based on cyclization of short DNA fragments, which allows very accurate determination of a. Our approach was based on assigning specific values of a to each of 10 distinct dinucleotide steps. We prepared DNA fragments, each about 200 bp in length, with various quasiperiodic sequences, measured their cyclization efficiencies (j f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
247
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(280 citation statements)
references
References 50 publications
(66 reference statements)
27
247
3
Order By: Relevance
“…This distance is the minimum observed in naturally occurring DNA loops, although smaller loops have been shown to function in artificial lac constructs (89). Ninety base pairs is distinctly shorter than the persistence length for DNA, which is about 150 bp for naked DNA (90), as usually measured in vitro by cyclization assays (91,92). To make smaller loops, the curvature energy of the DNA becomes too great and the formation of the loop is not favorable.…”
Section: Are There Other Systems Using Dna Looping To Regulate Gene Ementioning
confidence: 99%
“…This distance is the minimum observed in naturally occurring DNA loops, although smaller loops have been shown to function in artificial lac constructs (89). Ninety base pairs is distinctly shorter than the persistence length for DNA, which is about 150 bp for naked DNA (90), as usually measured in vitro by cyclization assays (91,92). To make smaller loops, the curvature energy of the DNA becomes too great and the formation of the loop is not favorable.…”
Section: Are There Other Systems Using Dna Looping To Regulate Gene Ementioning
confidence: 99%
“…Other bulk experiments, such as DNA-cyclization [13,18] and gel electro-phoretic mobility [10,22], also result in a value in this range (Table I).…”
Section: Introductionmentioning
confidence: 85%
“…The most convenient measure of bending flexibility of a polymer is the "persistence length" (P ), which is defined as the correlation length of the tangent unit vector along the contour length [1]. Many experimental and simulational techniques have been performed to measure this quantity of the DNA molecule [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], and characterize its dependence on the ionic strength [2,10,11,17], temperature [12], sequence [18] and length scale [19][20][21]. In the single molecule stretching experiment, Baumann et al have shown that the persistence length of a random DNA sequence in moderate salt buffer is around 45−50 nm [11].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the location of the CarD binding site relative to the P QRS promoter region still remained to be addressed. We checked this by generating variants of the CarD binding site which moved the site by 5 bp or 10 bp upstream of the natural site at P QRS , corresponding to displacements of approximately one-half or one helical turn, respectively (28)(29)(30). Figure 5A depicts the specific site displacement variants that were examined.…”
Section: Resultsmentioning
confidence: 99%